2018
DOI: 10.1016/j.jid.2017.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of TRPV3 Impairs Heat-Evoked Vasodilation and Thermoregulation: A Critical Role of CGRP

Abstract: Sensing environmental temperature is a key factor allowing individuals to maintain thermal homeostasis via thermoregulatory mechanisms, including changes to skin blood flow. Among transient receptor potential channels, transient receptor potential vanilloid 3 (TRPV3) is a heat-activated cation channel highly expressed in keratinocytes. However, the role of TRPV3 in triggering heat-evoked cutaneous vasodilation is unknown. Using a murine in vivo model of local acute environmental heat exposure in the skin, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…In heterologous systems in vitro, TRPV3 opens at temperatures >33 °C [14,15], i.e., within the upper range of physiological values of T sk , as observed during skin vasodilation in rats [34]. Furthermore, TRPV3 has been reported to mediate the cutaneous vasodilatation induced by local heating and to play a role in defending the deep T b during heat exposure [35]. Other studies suggest that TRPV3 is involved in the avoidance of innocuous ambient heat in transgenic mice, as well as in thermal pain responses [19,36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In heterologous systems in vitro, TRPV3 opens at temperatures >33 °C [14,15], i.e., within the upper range of physiological values of T sk , as observed during skin vasodilation in rats [34]. Furthermore, TRPV3 has been reported to mediate the cutaneous vasodilatation induced by local heating and to play a role in defending the deep T b during heat exposure [35]. Other studies suggest that TRPV3 is involved in the avoidance of innocuous ambient heat in transgenic mice, as well as in thermal pain responses [19,36].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies suggest that TRPV3 is involved in the avoidance of innocuous ambient heat in transgenic mice, as well as in thermal pain responses [19,36]. Yet, TRPV3 knockout mice show no obvious thermoregulatory phenotype [37] and, specifically, no alterations in the deep T b [19,35]. Overall, there is no consensus as to whether TRPV3 is important in driving thermoregulatory responses, and which responses in particular [16].…”
Section: Discussionmentioning
confidence: 99%
“…However, besides this aspect, keratinocytes have been shown to be directly involved in cutaneous sensoriality. Indeed, they can both modulate and initiate sensory perception and sensory neuron response [21,42,43]. Thus, an appropriate model to study skin sensitivity and assess active molecule efficacy on sensitive skin needs to at least contain sensory neurons and keratinocytes (Table 1).…”
Section: Sensory Neuron Culture and Coculturementioning
confidence: 99%
“…Nevertheless, some studies revealed that keratinocytes also express diverse sensory receptors, such as TRPV1, TRPV3, and TRPV4 [8,11,20]. Mainly expressed in keratinocytes, TRPV3 can stimulate CGRP secretion, which induces local vasodilation that plays a role in body thermoregulation [21]. The selective activation of the keratinocyte-located TRPV1 and TRPV4 sensors is sufficient to induce pain and itch, respectively [11].…”
Section: Introductionmentioning
confidence: 99%
“…Infrared thermal imaging is generally used to capture surface temperature estimates of objects for inference of heat transfer (Tattersall 2016). It has the practical advantage of being non-invasive and yet still provides quantitative thermal information, from which inferences of surface blood flow (Di Carlo 1995;Fromy et al 2018), evaporative cooling (Cadena et al 2013), and localized heat production (Robertson et al 2019) have been recorded. Thermal imaging cameras are capable of both still image and video capture, although typically video capture requires computer-assisted image capture.…”
Section: Introductionmentioning
confidence: 99%